Implementation of Human Resource Management (HRM) In Improving Teacher Performance and Insuring Education Quality - Saiddaeni; Muhammad Fajar Tri Santoso; Muhammad Munadi (Fakultas Ilmu Tarbiyah dan Keguruan (FITK), Institut Agama Islam Negeri (IAIN) Surakarta, 2023)
In an effort to advance a school, human resource management, especially educators, has a very crucial role. The quality of education refers not only to the end result, but also to the learning process and the human resources involved. In measuring the quality of education, it is necessary to consider a number of factors, ranging from inputs, namely the quality of students and school infrastructure, the learning process that takes place in the classroom, to outputs, namely students' academic achievement and readiness to face future challenges. This study aims to understand the practices, policies and concrete steps taken by SMP 1 Kalikotes towards Human Resource Management (HR) for Islamic Religious Education Teachers (Guru Pendidikan Agama Islam). By focusing on the implementation of teacher resource management, this research will provide information, this research will provide information in revealing the best practices and challenges faced by the school in an effort to improve the quality of education. Field research is a relevant approach to explore the dynamics and challenges faced by schools in managing teacher human resources to improve the quality of education. This research will adopt a case study research design. The results of our research show that SMP 1 Kalikotes Klaten has made significant efforts in teacher training, both through internal and external training. The program of making teaching modules and implementing the independent curriculum is well designed and in accordance with the needs of teachers, helping to improve skills and knowledge in the teaching process.